Evaluation of mechanical and structural behavior of austenitic and duplex stainless steel reinforcements. (1st March 2015) - Medina, Eduardo; Medina, Juan Manuel; Cobo, Alfonso; Bastidas, David M.
Graphical abstract: Highlights: Stainless steel (SS) reinforcements offer high ductility performance to fracture. SS reinforced concrete provides long-lasting constructions and buildings. SS reinforcements show higher ductility than carbon steel (CS) when hot rolled. SS reinforcements reach a slightly lower modulus of elasticity than CS. Abstract: The mechanical and structural behavior of three stainless steel (SS) reinforcing bars (austenitic AISI 304, duplex AISI 2304 and new lean duplex AISI 2001) have been studied and compared with the conventional carbon steel (CS) B500SD. The study was conducted at rebar level, cross-section level and structural member level. The results demonstrate higher ductility performance for hot-rolled SS rebars than for CS, but lower ductility for cold-rolled SS rebars compared to CS. The experimental elastic modulus of SS rebars is lower than that of CS.